Exploring HIV-Related Stigma as a Determinant of Engagement in HIV Care by African American Women. (March 2020) - McCoy, Katryna; Lipira, Lauren; Kemp, Christopher G.; Nevin, Paul E.; Huh, David; M. Turan, Janet; Mugavero, Michael J.; Cohn, Susan E.; Bahk, Mieoak; Simoni, Jane M.; Andrasik, Michele P.; Rao, Deepa
Abstract: Engagement in HIV care reduces HIV-related health disparities that persist across racial/ethnic and gender lines; yet, African American (AA) women face multiple challenges to remaining engaged in care, including HIV-related stigma. We analyzed longitudinal data from 239 participants in the Unity Health Study to estimate associations between HIV-related stigma and engagement in care among AA women linked to HIV care. In adjusted Poisson regression analyses, engagement in care was not associated with HIV-related stigma but was associated with older age (incidence rate ratio [IRR] = 1.01, 95% confidence interval [CI] = [1.00–1.01], p = .01), higher levels of education (IRR = 1.18, 95% CI = [1.02–1.35], p = .03), and higher levels of social support (IRR = 1.05, 95% CI = [1.01–1.09], p = .04). Our findings suggest the need for targeted interventions to enhance engagement in care and to incorporate social support into health promotion programming for AA women living with HIV.